Pemanfaatan Limbah Dapur Organik Pada Kelompok Ibu-Ibu Rumah Tangga Kelurahan Sukur Kecamatan Airmadidi Kabupaten Minahasa Utara: Utilization of Organic Kitchen Waste in the Group of Housewives, Sukur Village, Airmadidi District North Minahasa Regency (Tumou Tou: Jurnal Pengabdian Masyarakat, 2023)
The application of 3R or reduce, reuse and recycle waste is one of the best programs in the context of preserving the living environment because it prioritizes handling waste from the source. An effective way to realize waste management is by making multi-use liquids that can be applied at the household level. The implementation of the community partnership program involves partner groups of housewives in Sukur Village, Airmadidi District, North Minahasa Regency in the form of socialization and training on making multipurpose liquids. eco enzyme. Organic kitchen waste that is processed in the form of fruit peels (papaya, pineapple, avocado, sunkiss orange, lemon cui, carrots, apples, soursop, manggo and cabbage). The fermentation process lasts for 3 months. The results of making the harvested Eco-enzyme meet the standard pH < 4.0, namely 3.2 and 3.8. Thus, the production of eco-enzymes from the group of housewives in Sukur Village went well, there were no maggots and fungi. Eco-enzyme stored in the shade and ready to use. Eco-enzymes do not expire and last forever.